2018
DOI: 10.1016/j.appet.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

The Montreal Children’s Hospital Feeding Scale: Relationships with parental report of child eating behaviours and observed feeding interactions

Abstract: MCHFS showed good criterion validity with other parental report measures of eating and observations of mealtime interactions. MCHFS may be a useful tool for researching feeding problems in community samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 59 publications
5
24
0
3
Order By: Relevance
“…In examining the possible influencing factors, consistent with Van Dijk's study, we found that feeding difficulty was more prominent in older children (28). A higher incidence was also reported in girls in our study, while no gender difference has been reported in previous studies (10,17,37). In addition, it has been suggested that a variety of prenatal and perinatal, medical, environmental, and parental factors may be related to feeding problems (38)(39)(40).…”
Section: Discussionsupporting
confidence: 90%
“…In examining the possible influencing factors, consistent with Van Dijk's study, we found that feeding difficulty was more prominent in older children (28). A higher incidence was also reported in girls in our study, while no gender difference has been reported in previous studies (10,17,37). In addition, it has been suggested that a variety of prenatal and perinatal, medical, environmental, and parental factors may be related to feeding problems (38)(39)(40).…”
Section: Discussionsupporting
confidence: 90%
“…The Feeding Interaction Scale (FIS; Wolke, Sumner, McDermott, & Skuse, ) was used to code maternal behaviours during the mealtime observation (Table details subscales used and behaviours assessed). This FIS has clinical validity and has been used to assess maternal–infant feeding interactions and diagnose feeding problems (Farrow & Blissett, ; Lindberg, Bohlin, Hagekull, & Palmerus, ; Rogers & Blissett, ; Rogers, Ramsay, & Blissett, ; Skuse, Wolke, & Reilly, ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, the CEBQ was found to be accurate at discriminating between fussy and non-fussy eaters who were categorised using a structured parent interview (Steinsbekk, Hamre Sveen, Fildes, Llewellyn, & Wichstrøm, 2017). Similarly, Rogers, Ramsey and Blissett (2018) found the CEBQ FF subscale to have good criterion validity with the Montreal Children's Hospital Feeding Scale (MCHFS; Ramsay, Martel, Porporino & Zygmuntowicz, 2011), a brief 14 item parent-report measure of children's feeding problems.…”
Section: Introductionmentioning
confidence: 93%